P5-S4.06 Sticking to it: the effect of maximally assisted therapy on antiretroviral treatment adherence among a cohort of unstably housed people living with HIV in BC, Canada. (10th July 2011) - Parashar, S; Palmer, A; O'Brien, N; Chan, K; Shen, A; Coulter, S; Montaner, J; Hogg, R
Abstract : Background: Housing is a known determinant of health behaviour, including adherence to antiretroviral therapy. Within the Longitudinal Investigations into Supportive and Ancillary Health Services (LISA) cohort, unstable housing is inversely associated with adherence. The Maximally Assisted Therapy (MAT) program uses a multidisciplinary approach to support people living with HIV/AIDS (PHA) who have a history of addictions, mental health disorders and homelessness. We investigated the efficacy of support services, including the MAT program, in improving adherence for unstably housed PHA. Methods: The LISA cohort is a cross-sectional study of individuals on antiretroviral therapy in British Columbia. Interviewer-administered surveys collect information regarding housing, drug use, utilisation of health services and other clinically relevant socio-demographic factors. Clinical variables, such as CD4 count and viral load, were obtained through longitudinal linkages with the Drug Treatment Program (DTP) at the BC Centre for Excellence in HIV/AIDS. Logistic regression was used to determine factors associated with adherence (≥95% vs <95%) among unstably housed LISA participants (n=212). Results: Between 2007 and 2010 approximately 1000 participants were interviewed. This analysis is based on 644 interviews, of which the DTP reports optimal adherence [≥95% 12 month refill] for 367 (57%) individuals. Median age was 46 and 475 (73.7%) were male. We found that unstably housed participants attending the MAT program were 4.76 times more likely to be ≥95% adherent [95% CI 1.72 to 13.13] than those who did not. Other factors associated with optimal adherence included recent incarceration (Adjusted OR [AOR]=0.20 [95% CI 0.05 to 0.80]) and not currently using illicit drugs (AOR=0.40 [95% CI 0.16 to 0.99]). Conclusion: The MAT program provides a model for other urban centers dealing with concurrent and interrelated adherence barriers: high-risk drug use, mental health disorders and homelessness. In the absence of sustainable housing solutions, programs such as MAT are crucial to achieving optimal treatment adherence in this population.